Milkweed Assassin Bug (Suggested Common Name) Zelus longipes Linnaeus (Insecta: Hemiptera: Reduviidae) - Megha Kalsi; Dakshina R. Seal (EDIS, 2011)
Commonly called the milkweed assassin bug, because it closely resembles the milkweed bug, it is also known as the longlegged assassin bug and the Zelus assassin bug. Members of the genus Zelus belong to the subfamily Harpactorinae and are diurnal in nature. They are generalist predators feeding on a wide range of soft-bodied prey in garden and fields, such as mosquitoes, flies, earthworms, cucumber beetles, and caterpillars (fall armyworm, rootworm, etc.) Learn more in this 7-page fact sheet written by Megha Kalsi and Dakshina R. Seal and published by the UF Department of Entomology and Nematology Department, February 2011.